Theologen van de twintigste eeuw en de christologie - A. van de Beek (Acta Theologica)
Theologically the twentieth century can be conceived as a century of Christology. In order to fill in the background for this, we first sketch the opposite position, in Arnold Van Ruler’s idea of Christ as an emergency measure. Van Ruler was, however, one of the rare theologians in the core of the twentieth century who resisted the wave of Christological thought that was initiated by Karl Barth. Barth firmly stated that Christ is the only source of revelation, and thus theology depends fully on Christology. Even Emil Brunner’s idea of ‘truth in encounter’ (which is sketched in §3) was opposed by a strict ‘No’ from Barth.